Extreme weather and social vulnerability in colonial Antigua, Lesser Antilles, 1770-1890 - Berland, Alexander Jorge (2015)
This thesis presents an history of extreme climate events in Antigua, a former British colony in the Lesser Antilles, spanning the years 1770-1890. It employs a range of documentary sources from that period, including government, plantation, missionary and scholarly papers. Two major empirical elements are addressed: (1) reconstruction of the timing and magnitude of precipitation variability and tropical cyclone activity and (2) investigation of the implications of climatic hazards—principally droughts and hurricanes—for Antiguan society. On the basis of these analyses, temporal and social patterns of human vulnerability to hydrological extremes and storms are explored.